Fold changes in relative mRNA expression of immune response genes in lymphoid tissues of Rhode Island Red chicken - RAHIM, ABDUL; KUMAR, SANJEEV; DEBNATH, JOWEL; YADAV, RAMJI; DAS, ANANTA KUMAR; YADAV, A S (The Indian Journal of Animal Sciences, 2017)
Fold changes in relative mRNA expression of three immune response genes viz. IL1–β, iNOS and TLR15 were determined in bursa, spleen and thymus tissues of Rhode Island Red chicken. Total RNA was isolated from 12 birds, aged around 6–8 weeks. Relative quantification of mRNA expression was assessed by qRT-PCR. Fold expressions were determined using average threshold cycle (Ct) values employing 2(–∆∆Ct) method. There was wide variation in basal expression levels of immune response genes among different tissues. Basal mRNA expression of IL1–β, iNOS and TLR15 genes was several folds higher in bursa than in spleen and thymus. This investigation has generated important findings related to immune response genes expression which could pave way to further investigation in host-pathogen genetics and finally to develop breeding strategies for improvement of diseases resistance so as to have better protection and production in chicken.